2014
DOI: 10.1017/s1368980014001414
|View full text |Cite
|
Sign up to set email alerts
|

Food security status among grade 5 students in Nova Scotia, Canada and its association with health outcomes

Abstract: Objective: Food security (FS) exists when all people, at all times, have physical and economic access to sufficient, safe and nutritious food to meet their needs. The present research sought to determine whether students from households experiencing moderate or severe food insecurity (FI) had poorer diet quality, higher body weights and poorer psychosocial outcomes than students from households classed as having high FS or marginal FI status. Design: Population-based survey conducted in schools. Multiple regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 38 publications
1
37
2
Order By: Relevance
“…7 Since then, research has not shown a clear pattern in the relationships among hunger, food insecurity and overweight in children, with varying results depending on the age range, gender and ethnic distribution of the samples. 6,9,13 In Canada, a higher level of child overweight/ obesity among food-insecure families compared to others was reported in Quebec, 22,23 among Aboriginal children, 24 among grade 5 students in Nova Scotia, 25 and among a large sample of youth aged 9-18 across Canadian provinces in 2004 (territories excluded). 26 Our study adds to this body of evidence by showing that hunger relates to excess body weight in children aged 11-15 years, even after controlling for potential confounders related to the socio-economic status of the child (such as family affluence and structure, ethnicity and school neighbourhood environment), and with a significant but weaker association after full adjustment for child lifestyle behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…7 Since then, research has not shown a clear pattern in the relationships among hunger, food insecurity and overweight in children, with varying results depending on the age range, gender and ethnic distribution of the samples. 6,9,13 In Canada, a higher level of child overweight/ obesity among food-insecure families compared to others was reported in Quebec, 22,23 among Aboriginal children, 24 among grade 5 students in Nova Scotia, 25 and among a large sample of youth aged 9-18 across Canadian provinces in 2004 (territories excluded). 26 Our study adds to this body of evidence by showing that hunger relates to excess body weight in children aged 11-15 years, even after controlling for potential confounders related to the socio-economic status of the child (such as family affluence and structure, ethnicity and school neighbourhood environment), and with a significant but weaker association after full adjustment for child lifestyle behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Food insecurity in Canada is linked with higher rates of self-reported poor health and chronic health conditions, including depression, type 2 diabetes, heart disease, and greater stress [25]. Several studies have reported that food-insecure households are at risk of having monotonous and low-quality diets, reduced micronutrient intake, iron-deficiency anemia, and low intake of fruits, vegetables, and dairy products, particularly among women and youth [26].…”
Section: Food Insecurity and Healthmentioning
confidence: 99%
“…Food insecurity has been linked with higher rates of self-reported poor health and chronic health conditions, including depression, hypertension, type 2 diabetes, and heart disease [25,[30][31][32][33][34]. For instance, findings from a recent study which explored the associations between food security status (high food security; marginal, moderate, or severe food insecurity), dietary behaviors and intake, and health-related outcomes (body weight, quality of life, mood, peer relationships, and externalizing problems) in 5853 Nova Scotian grade 5 students [25] suggested that students living in households experiencing moderate or severe food insecurity had poorer diet quality, higher body mass index, and poorer psychosocial outcomes than students living in households classified as high food secure or marginal food insecure [25].…”
Section: Food Insecurity and Chronic Health Conditionsmentioning
confidence: 99%
“…Although findings from a number of previous studies generally agree that HFI is associated with poorer psychosocial functioning in US and Canadian school-aged children [ 9 16 ], disagreement exists with respect to the specific types of psychosocial dysfunction involved. For example, some [ 5 , 9 , 11 , 14 , 16 ] but not all studies [ 25 , 26 ] linked HFI with greater internalizing behavior. Likewise, some authors reported that HFI is associated with increased externalizing/aggressive behaviors [ 5 , 9 , 11 , 13 , 26 , 27 ] but several others did not [ 16 , 25 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In school-age children, it also has been linked to feelings of deprivation, shame [ 7 ], suboptimal academic performance, and poorer social skills [ 8 ]. The findings from a number of prior studies conducted in the US and Canada suggest that school-age children exposed to HFI have greater psychosocial dysfunction [ 9 16 ]. This is important since psychosocial dysfunction is a major cause of childhood disability that can adversely affect normal child development, social relations, academic performance, and quality of life.…”
Section: Introductionmentioning
confidence: 99%